Economic Challenges of Drinking Water Loss in Bulgaria - Stoyanova, Desislava (Research Papers, 2025)
Drinking water management in Bulgaria is one of the main priorities at the state and local level. The purpose of the study is to define the main economic challenges by analyzing the loss of drinking water and its impact on the country`s economy. A comparative and structural analysis of the delivered and invoiced quantities of water under basin management has been applied, establishing losses in the range of 52-62% for 2023. The analysis clarifies the consequences of inefficient drinking water management, the economic challenges of introducing digital tools and their impact on the end user. Official statistical data were used for the purposes of the analysis. Good practices and conclusions for sustainable drinking water management in Bulgaria are presented.